Palaeocene–Eocene Thermal Maximum prolonged by fossil carbon oxidation. Issue 1 (January 2019) - Lyons, Shelby; Baczynski, Allison; Babila, Tali; Bralower, Timothy; Hajek, Elizabeth; Kump, Lee; Polites, Ellen; Self-Trail, Jean; Trampush, Sheila; Vornlocher, Jamie; Zachos, James; Freeman, Katherine
Abstract A hallmark of the rapid and massive release of carbon during the Palaeocene–Eocene Thermal Maximum is the global negative carbon isotope excursion. The delayed recovery of the carbon isotope excursion, however, indicates that CO2 inputs continued well after the initial rapid onset, although there is no consensus about the source of this secondary carbon. Here we suggest this secondary input might have derived partly from the oxidation of remobilized sedimentary fossil carbon. We measured the biomarker indicators of thermal maturation in shelf records from the US Mid-Atlantic coast, constructed biomarker mixing models to constrain the amount of fossil carbon in US Mid-Atlantic and Tanzania coastal records, estimated the fossil carbon accumulation rate in coastal sediments and determined the range of global CO2 release from fossil carbon reservoirs. This work provides evidence for an order of magnitude increase in fossil carbon delivery to the oceans that began ~10–20 kyr after the event onset and demonstrates that the oxidation of remobilized fossil carbon released between 102 and 104 PgC as CO2 during the body of the Palaeocene–Eocene Thermal Maximum. The estimated mass is sufficient to have sustained the elevated atmospheric CO2 levels required by the prolonged global carbon isotope excursion. Even after considering uncertainties in the sedimentation rates, these results indicate that the enhanced erosion, mobilization and oxidation of ancient sedimentary carbon contributed to the delayed recovery of the climate system for many thousands of years. Delivery of fossil carbon to the oceans strongly increased about 15 kyr after the onset of the Palaeocene–Eocene Thermal Maximum as a result of oxidation of sedimentary carbon, suggests an analysis of geochemical measurements with a biomarker mixing model.